Hybrid Capture-Based Next Generation Sequencing and Its Application to Human Infectious Diseases - Gaudin, Maxime; Desnues, Christelle (Frontiers in Microbiology, 2018)
This review describes target-enrichment approaches followed by next generation sequencing and their recent application to the research and diagnostic field of modern and past infectious human diseases caused by viruses, bacteria, parasites and fungi.